2000
DOI: 10.1016/s1097-2765(00)80403-7
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog Creates a Gradient of DPP Activity in Drosophila Wing Imaginal Discs

Abstract: Hedgehog (HH) and Decapentaplegic (DPP) direct anteroposterior patterning in the developing Drosophila wing by functioning as short- and long-range morphogens, respectively. Here, we show that the activity of DPP is graded and is directly regulated by a novel HH-dependent mechanism. DPP activity was monitored by visualizing the activated form of Mothers against dpp (MAD), a cytoplasmic transducer of DPP signaling. We found that activated MAD levels are highest near the source of DPP but are unexpectedly low in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
358
0
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 381 publications
(380 citation statements)
references
References 66 publications
15
358
0
3
Order By: Relevance
“…In the wild-type wing discs, pMad levels are high in the center, and then graded towards the peripheral region of the wing pouch as observed by immunostaining (Figure 1A), consistent with other’s reports [54]. Over expression of ban along the A/P boundary in the wing imaginal disc by ptc-Gal4 resulted in greatly decreased pMad levels along the A/P boundary in these animals (Figure 1B).…”
Section: Resultssupporting
confidence: 90%
“…In the wild-type wing discs, pMad levels are high in the center, and then graded towards the peripheral region of the wing pouch as observed by immunostaining (Figure 1A), consistent with other’s reports [54]. Over expression of ban along the A/P boundary in the wing imaginal disc by ptc-Gal4 resulted in greatly decreased pMad levels along the A/P boundary in these animals (Figure 1B).…”
Section: Resultssupporting
confidence: 90%
“…Because GSCs require a Dpp signal to maintain their stem cell identity, we reasoned that the niche can be no larger that the region capable of stimulating a competent germ cell to activate its Dpp pathway. Immunostaining of wild-type ovarioles with pMAD (22) revealed that only GSCs and possibly CBs activate the Dpp pathway at the highest levels (Fig. 1c, arrowhead).…”
Section: Resultsmentioning
confidence: 99%
“…hh-Gal4, hh-nlsDsRed and ptc-Gal4 enhancer trap lines express in wing discs in patterns that mimic hh and ptc, respectively (Akimoto et al, 2005;RamirezWeber et al, 2000;Tanimoto et al, 2000). Stocks were obtained from Bloomington Drosophila Stock Center (BDSC): UAS-disp RNAi (#27247), UAS-dia RNAi (#28541), tub-Gal80 ts (#7018), UAS-CD8:GFP (#5137), yw, ubi-RFP.nls FRT40A/CyO (#34500) and UAS-Nrg RNAi (#37496).…”
Section: Drosophila Stocksmentioning
confidence: 99%